Sympathetic Nerve Function Status in Obesity - Akhter, Shahin; Begum, Noorzahan; Ferdousi, Sultana; Begum, Shelina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2010)
Background: Obesity is an important and independent risk factor for cardiovascular morbidity and mortality. High incidence of cardiac autonomic nerve dysfunction has been noted in obese subjects who are at increased risk for sudden death Objective: To study the relationship between sympathetic nerve function and obesity. Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University between July 2006 to June 2007 and 40 apparently healthy obese subjects aged 18-40 years of both sexes with BMI ≤ 25 kg/m2 in study group. Age and sex matched 40 apparently healthy nonobese subjects with BMI range of 18.5-22.9 kg/m2 were also included for comparison (Control). Two noninvasive cardiovascular reflex tests like blood pressure response to sustained handgrip and blood pressure response to standing were done to assess sympathetic nerve function status. Unpaired Student's 't' test and Pearson correlation coefficient test were used for statistical analysis. Results: Mean values of resting heart rate, resting systolic and diastolic blood pressure were significantly (p<0.05) higher and both the sympathetic nerve function parameters (BP response to hand grip and BP response to standing) were significantly (p>0.05) lower in obese compared to those of non obese control subjects. Again, BP response to hand grip were negatively and BP response to standing were positively correlated with BMI in all subjects. These correlations are statistically significant (p<0.05). Conclusion: The results of this study revealed that sympathetic nerve function may be reduced in obesity. Key words: sympathetic nerve function; obesity; BMI DOI: 10.3329/jbsp.v5i1.5416 J Bangladesh Soc Physiol. 2010 June; 5(1): 34-39